BLACK SEA TRAGEDY (The Black Sea Fleet in the Political Vortex of 1917-1918) - Victor Ivanovich Korolev (Проблемы постсоветского пространства, 2017)
From the time of disintegration of the former USSR and to the present time the Black Sea fleet was and still is in the focus of interstate relationships and political struggle. This paper studies the whole range of multiple political parties and national organizations that were active on the fleet in 1917-1918 and in the Sevastopol garrison.